KEMUNDURAN PENDIDIKAN ISLAM PADA PERIODE PERTENGAHAN: ANALISIS SOSIAL POLITIK, FAKTOR PENYEBAB, DAN TRANSFORMASI PENDIDIKAN - Muh Akbar; Syamsuddin; Munirah (Istiqra: jurnal hasil penelitian, 2025)
The role of language editing in students’ language comprehension is becoming increasingly important. Reading and writing are the primary activities in language learning, and with proper language editing, students can enhance their understanding of the language and develop their language skills. This study aims to enhance students’ language comprehension by examining the role and implications of language editing. This study uses qualitative literature research, with data sources such as books and journal articles, employing a documentary approach, and is analyzed using descriptive or analytical techniques. The results of this study show that language editing enhances students’ language comprehension by improving grammar, expanding vocabulary, clarifying the relationship between vocabulary and meaning, and improving students’ communication.